Center Will Hold - Pemberton, Michael (University Press of Colorado, 2003)
In The Center Will Hold, Pemberton and Kinkead have compiled a major volume of essays on the signal issues of scholarship that have established the writing center field and that the field must successfully address in the coming decade. The new century opens with new institutional, demographic, and financial challenges, and writing centers, in order to hold and extend their contribution to research, teaching, and service, must continuously engage those challenges. Appropriately, the editors offer the work of Muriel Harris as a key pivot point in the emergence of writing centers as sites of pedagogy and research. The volume develops themes that Harris first brought to the field, and contributors here offer explicit recognition of the role that Harris has played in the development of writing center theory and practice. But they also use her work as a springboard from which to provide reflective, descriptive, and predictive looks at the field.